PENGARUH MODEL PEMBELAJARAN KNISLEY TERHADAP AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 43 PADANG - Melisa - (Departemen Matematika, 2019)
The activities and results of mathematics learning in class VIII SMP Negeri 43 Padang were still low. The reason is students are lazy to do the exercises given. Therefore, we need a learning model that can improve learning outcomes, namely Knisley Learning Model. The Knisley Learning Model is a learning model consisting of four stages where there is a division of roles between teacher and students. This study aims to describe how student learning activities during the implementation of and find out whether the learning outcomes of students who learn to apply Knisley Learning Model are better than students who study with conventional learning in class VIII of SMP Negeri 43 Padang. The results of processing and data analysis show that student learning activities experience fluctuations for each meeting. Based on the analysis of the final test results, at the real level α = 0.05, it can be concluded that the mathematics learning outcomes of students who study with Knisley Learning Model are better than the learning outcomes of students who study with conventional learning in SMP Negeri 43 Padang.Keywords— activities, result study, Knisley, Knisley Learning Model